MARKING THE MARGINS: KAZAKHSTANI LITERATURE FROM COLLAPSE TO INDEPENDENCE - Anderson, Aida (Nazarbayev University School of Sciences and Humanities, 2025)
Abstract: This thesis examines the transformation of post-Soviet Kazakhstani literature through the work of Olga Markova and her literary foundation, Musaget. Following the collapse of the Soviet Union, Kazakhstan experienced not only political and economic upheaval, but also a deep cultural and institutional vacuum. Former centers of literary authority, such as the Writers’ Union, were rendered functionally obsolete, and contemporary authors were left without infrastructure, community, or recognition. Drawing on oral histories, archival materials, and theoretical frameworks from Bourdieu, Groys, Dobrenko, Clark, Yurchak, and Oushakine, this thesis explores how new forms of literary legitimacy emerged in response to this collapse. Chapter 1 traces Markova’s early life, focusing on how her experience of disability and marginalization shaped her intellectual vision. Chapter 2 analyzes the disintegration of literary institutions and Markova’s response: the creation of Musaget as a counter-institution devoted to aesthetic rigor, formal experimentation, and the cultivation of new writers. Through its seminars, journal Apollinarii, and peer-led critique sessions, Musaget became a center for literary innovation in Kazakhstan at a time when cultural life had largely stagnated. The thesis argues that marginality — linguistic, institutional, and cultural — served as a generative force, enabling Markova and her circle to reimagine literature’s purpose. Rather than replicating the structures of the past, they sought to restore meaning and artistic discipline in a radically changed environment. This case study contributes to the study of post-Soviet cultural life by revealing how literary authority can be rebuilt through vision, community, and commitment to form.
Казахстанская МАРКа: литература от распада к независимости
Шеттердегі МАРКа: Қазақстандық әдебиеттің күйреуден тәуелсіздекке дейін жолы
Keywords: HUMANITIES and RELIGION::Aesthetic subjects::Literature; Kazakhstan; SOCIAL SCIENCES::Social sciences::Social work::Disability research; Marginality; Russophonia; type of access: embargo